Investigation of the factors affecting mother’s exclusive breastfeeding for six months - Yüzügüllü, Didem Ata (Turk Pediatri Ars, 2018)
AIM: The aim of this study is to investigate the socio-demographic characteristics and psychopathologic features of mothers living in Cukurova, Adana and to investigate the effect of these characteristics on exclusive breastfeeding status for the first six months. MATERIAL AND METHODS: This is a cross sectional study. 284 randomly selected women were reached in the study, between November 2015–February 2016. A questionnaire consisting of 27 questions which determine sociodemographic characteristics and brief symptom inventory were applied. As for the statistical evaluation, SPSS 19 Package Software for Windows was used. For the statistical analysis; frequency tables, average scores from the brief symptom inventory, chi square test, Mann-Whitney U and Multiple logistic regression analysis were used. RESULTS: 37.0% of the mothers gave exclusive breastfeeding for first six months. Those who graduated from high school and upper school, those who were educated in breastfeeding, those who breastfed for the half hour after birth, and those who did not work had a significantly higher rate of giving only breast milk for the six months. However, the rate of breastfeeding in first six months was significantly lower for women those who lived together with their elders and smokers. The mean scores from brief symptom inventory were significantly higher in mothers who did not give breast milk only during first six months. CONCLUSION: Exclusive breastfeeding rate was 37% in the first six months of our study. The postpartum period is a period in which the risk of psychiatric discomfort increases and the mother should be supported.